Use of endoscopic submucosal dissection or full-thickness resection device to treat residual colorectal neoplasia after endoscopic resection: a multicenter historical cohort study - Yzet, Clara; Le Baleur, Yann; Albouys, Jérémie; Jacques, Jérémie; Doumbe-Mandengue, Paul; Barret, Maximilien; Abou Ali, Einas; Schaefer, Marion; Chevaux, Jean-Baptiste; Leblanc, Sarah; Lepillez, Vincent; Privat, Jocelyn; Degand, Thibault; Wallenhorst, Timothée; Rivory, Jérôme; Chaput, Ulriikka; Berger, Arthur; Aziz, Karim; Rahmi, Gabriel; Coron, Emmanuel; Kull, Eric; Caillo, Ludovic; Vanbiervliet, Geoffroy; Koch, Stéphane; Subtil, Fabien; Pioche, Mathieu (Endoscopy, 2023)
Introduction Residual colorectal neoplasia (RCN) after previous endoscopic mucosal resection is a frequent challenge. Different management techniques are feasible including endoscopic full-thickness resection using the full-thickness resection device (FTRD) system and endoscopic submucosal dissection (ESD). We aimed to compare the efficacy and safety of these two techniques for the treatment of such lesions.Methods All consecutive patients with RCN treated either using the FTRD or by ESD were retrospectively included in this multicenter study. The primary outcome was the R0 resection rate, defined as an en bloc resection with histologically tumor-free lateral and deep margins.Results 275 patients (median age 70 years; 160 men) who underwent 177 ESD and 98 FTRD procedures for RCN were included. R0 resection was achieved in 83.3 % and 77.6 % for ESD and FTRD, respectively (P = 0.25). Lesions treated by ESD were however larger than those treated by FTRD (P < 0.001). The R0 rates for lesions of 20–30 mm were 83.9 % and 57.1 % in the ESD and FTRD groups, respectively, and for lesions of 30–40 mm were 93.6 % and 33.3 %, respectively. On multivariable analysis, ESD procedures were associated with statistically higher en bloc and R0 resection rates after adjustment for lesion size (P = 0.02 and P < 0.001, respectively). The adverse event rate was higher in the ESD group (16.3 % vs. 5.1 %), mostly owing to intraoperative perforations.Conclusion ESD is effective in achieving R0 resection for RCN whatever the size and location of the lesions. When residual lesions are smaller than 20 mm, the FTRD is an effective alternative.